Effects of breed, management system, milk yield and body weight on onset of postpartum ovarian cyclicity in cows (Bangladesh Veterinarian, 2016)
To determine the factors affecting onset of postpartum ovarian cyclicity (PPOC) milk progesterone concentrations were measured in 84 cows. About 30% showed cyclicity within 120 days of parturition. Intensively managed cows started cyclicity earlier (P>0.05) than extensively managed animals. Holstein-Friesian crossbred cows started ovarian cyclicity earlier (80.2 ± 17.5 days) with higher proportion (37.9%) than local zebu cows (84.8 ± 21.0 days) and about 13.3%, respectively (P>0.05). The cows yielding 4-12 kg milk/day required 73.5 ± 10.0 days to start ovarian function earlier than those producing 1-2 kg/day (84.8 ± 21.0 days) (P>0.05). Cows with lower (300 kg) body weights started ovarian activity by 81.6 ± 16.6 and 76.3 ± 17.4 days, respectively (P>0.05). Cows with lower body weight showed PPOC at lower rate (5.2%) than those of medium (38.3%) and higher body weight (33.3%) (P